Research on Influencing Factors of Cross-Border E-commerce Enterprise Competitiveness (Asian Business Research, 2022)
The rise and prosperity of cross-border e-commerce has brought new development opportunities and greatchallenges to Chinese enterprises. By discussing the concepts and contents of cross-border e-commerce andenterprise competitiveness, this paper analyzes the influencing factors of enterprise competitiveness ofcross-border e-commerce enterprises. By means of questionnaires and interviews with the management ofrelevant enterprises, the relevant data were obtained. In the dimensional analysis of cross-border e-commerceand enterprise competitiveness, the influencing factors of cross-border e-commerce enterprise competitivenesswere discussed. The results show that the flat organizational structure is conducive to enhance thecompetitiveness of enterprises, and the fund management and human resource management play a more obviousrole; The mastery of key technologies brings competitive advantages to enterprises. Because laws andregulations belong to the policy environment, compared with other factors, the impact on the competitiveness ofenterprises is not obvious. To sum up, service level and customer satisfaction have the greatest impact onenterprise competitiveness; cost management and capital efficiency have a great impact on the competitivenessof enterprises; The conclusion that market demand has a relatively small impact on enterprise competitiveness.